KAJIAN FILOSOFI AQIQAH DAN UDHIYAH (PERSPEKIF ALQUR'AN DAN SUNNAH) - Hj. Nurnaningsih, Hj. Nurnaningsih (DIKTUM: Jurnal Syariah dan Hukum, 2013)
Aqiqah and Udhiyah which is a keyword in this paper are described by a system of philosophy, using descriptive qualitative method that aims to provide an understanding of all aspects related to the need for its implementation Syar’i and the conditions specified in the legal basis for al qur'an, Sunnah and ijma 'Ulama. There are several views about the need for the implementation of Aqiqah and Udhiyah so that in principle it can be said is a guidance Worship categorized in "Muakkad Sunnah, as well as benefit to be gained by doing that and instill a sense of piety and solidarity to make sense of sharing, especially among the poor in and orphans and also built the relationship on the other hand by eating sacrificial meat / aqiqah in unity with a view to get closer to Allah in achieving his Rida.